ROLE OF PARENTS IN MOTIVATING STUDENTS TO FOLLOW FUTTSAL EXTRACURCICAL ACTIVITIES - Ramadhan, Nala Nur (Jurnal Kesehatan Olahraga, 2018)
This study discusses the role of parents in motivating students to follow extracurricular activities futsal. This is because the extracurricular futsal in SMA Muhammadiyah 1 Sumenep has participants who are quite superior but not all of the participants are always present and serious to follow the training. The research method used in this study using quantitative descriptive method by using questionnaires to find out the results of research. The research subjects are the parents of SMA Muhammadiyah 1 Sumenep students, amounting to 30 people. The instrument used is a closed questionnaire containing statements that can motivate the child to follow extracurricular activities of futsal.Some of the role of parents in motivating their children is the parents know about futsal sports and include children in extracurricular activities futsal to cultivate talent and posture ananknya body. Parents also provide supporting facilities and always provide motivation and input for the development of his son's talents. With the inclusion of students into extracurricular activities, parents encourage their children to be able to add friends, more familiar with the teacher and gathered with his friends. Students are also encouraged by their parents to not be influenced by friends who can make them lazy to practice. For that their parents give gifts or rewards for the achievements achieved by their children.This is indicated based on data obtained from 30 respondents, there are 60% of parents really motivate their children with the answer of the average statement agree, then 40% of parents answer the average statement disagree in motivating students to follow extracurricular activities futsal. Thus most of the parents of the students did deliberately include their child in extracurricular activities futsal. So with the acquisition can be seen that the parents of SMA Muhammadiyah 1 Sumenep have a role and approve his son to follow extracurricular activities futsal, and hope the school held a selection of the best players to be awarded the award plaque in order to make students more active in the practice.Keywords: Role of Parent, Motivation, Extracurricular.